2015
DOI: 10.1063/1.4935549
|View full text |Cite
|
Sign up to set email alerts
|

Novel silicon allotropes: Stability, mechanical, and electronic properties

Abstract: One quasi-direct gap phase (Amm2) and three indirect gap phases (C2/m-16, C2/m-20, and I-4) of silicon allotropes are proposed. The detailed theoretical study on the structure, density of states, elastic properties, sound velocities, and Debye temperature of these four phases is carried out by using first principles calculations. The elastic constants of these four phases are calculated by strain-stress method. The elastic constants and the phonon calculations manifest all novel silicon allotropes in this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Four additional semiconducting low-energy silicon phases were reported by Fan et al: Amm2 (oA20), C2/m (mC16), C2/m (mC20), and I 4 (tI28). 97 All four structures were reported previously for carbon. 98 The calculations at the GGA-based DFT level revealed that the Amm2 silicon phase has a quasidirect band gap of 0.742 eV and a formation energy of 0.109 eV/atom.…”
Section: B Many New Forms Of Silicon Are Plausiblementioning
confidence: 99%
“…Four additional semiconducting low-energy silicon phases were reported by Fan et al: Amm2 (oA20), C2/m (mC16), C2/m (mC20), and I 4 (tI28). 97 All four structures were reported previously for carbon. 98 The calculations at the GGA-based DFT level revealed that the Amm2 silicon phase has a quasidirect band gap of 0.742 eV and a formation energy of 0.109 eV/atom.…”
Section: B Many New Forms Of Silicon Are Plausiblementioning
confidence: 99%
“…The bulk modulus of P 2/ m -Si is slightly smaller than that of diamond silicon. The shear modulus of P 2/ m -Si is also slightly smaller than that of diamond silicon but is the greatest among those of P 2/ m -Si, C 2/ m -16 Si, C 2/ m -20 Si, and I -4 Si [10]. The hardness of a material can determine the plastic and elastic properties to some extent and can be predicted by following formula [34]:HV=2false(normalk2normalGfalse)0.585-3…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the elastic anisotropic of the material could be shown by the percentage of elastic anisotropy for the bulk modulus A B , the percentage of elastic anisotropy for the shear modulus A G , and the universal anisotropic index A U : A U = 5 G V / G R + B V / B R − 6, A B = ( B V − B R )/( B V + B R ), and A G = ( G V − G R )/( G V + G R ) [ 65 ]. The calculated values of A B , A G and A U of t -Si x Ge 3− x N 4 , c -Si x Ge 3− x N 4 , and m -Si x Ge 3− x N 4 ( x = 0, 1, 2, 3) alloys are all listed in Table 3 .…”
Section: Resultsmentioning
confidence: 99%